2019
DOI: 10.17073/0368-0797-2019-8-600-605
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of formation of automobile sheet roughness during temper rolling in shot-blasted rolls

Abstract: Известия высших учебных заведений. Черная металлургия. 2019. Том 62. № 8 УДК 621.771.07:621.787.6 ТЕОРЕТИЧЕСКИЙ АНАЛИЗ ФОРМИРОВАНИЯ ШЕРОХОВАТОСТИ АВТОМОБИЛЬНОГО ЛИСТА ПРИ ДРЕССИРОВКЕ В ВАЛКАХ ОБРАБОТАННЫХ ДРОБЬЮ Огарков Н.Н. 1 , д.т.н., профессор кафедры машин и технологий обработки давлением и машиностроения ( ogarkovnikolai@mail.ru ) Звягина Е.Ю. 1 , к.т.н., старший преподаватель кафедры машин и технологий обработки давлением и машиностроения ( zviagina_mmf@mail.ru ) Исмагилов Р.Р. 2 , к.т.н., ведущий специа… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In most technological schemes temper rolling is the final stage of the rolling process. Theoretical and experimental studies have shown that under certain conditions during temper rolling the roughness of the rolls is almost completely transferred to the strip [6]. That is, the micro-relief of the work rolls is printed on the strip (Fig.…”
mentioning
confidence: 99%
“…In most technological schemes temper rolling is the final stage of the rolling process. Theoretical and experimental studies have shown that under certain conditions during temper rolling the roughness of the rolls is almost completely transferred to the strip [6]. That is, the micro-relief of the work rolls is printed on the strip (Fig.…”
mentioning
confidence: 99%